The Importance of Tax Awareness: A Religiosity and Personality Perspective - Primandita FITRIANDI; Suratno SURATNO; Tri WIDYASTUTI (PT Keberlanjutan Strategis Indonesia, 2025)
Tax awareness in Indonesia is relatively low, with only 11% of the population having a Taxpayer Identification Number (NPWP), influenced by negative perceptions and a culture of tax avoidance. Educational and technological initiatives have begun to increase participation, but challenges remain, especially in remote areas. This study aims to explore the influence of religiosity and personality on taxpayer awareness. This study adopts a positivist approach, focusing on the measurement and causal relationships of empirical variables. The data for this study were obtained from primary data from 324 respondents. The results show that religiosity does not increase personal taxpayer awareness. Personality, on the other hand, has been shown to influence tax awareness. These findings suggest that tax compliance is more influenced by external factors, such as the quality of the tax system, than internal factors such as religious values. This study recommends tax policy reforms to increase transparency and efficiency, as well as educational campaigns that demonstrate the collective benefits of paying taxes for taxpayers.